Relationship of aggression, negative affect, substance use problems, and childhood delinquency to DWI recidivism. (2nd January 2016) - Linn, Braden K.; Nochajski, Thomas; Wieczorek, William
ABSTRACT: Background : Driving under the influence remains a pervasive problem. Approximately 30% of those arrested for impaired driving offenses each year are repeat offenders, suggesting that current rehabilitative efforts are not sufficiently effective for reducing driving while intoxicated (DWI) recidivism. Aggression, negative affect, substance use problems, and childhood delinquency have been noted in the population of impaired drivers, but study of these variables on recidivism has been limited. Objectives : The aim of the current study was to examine the effects of aggression, negative affect, substance use problems, and childhood delinquency on DWI recidivism among first time offenders. Methods : In 1992, 6436 individuals in impaired driver programs in New York State were surveyed. A total of 3511 individuals provided names so that state driver abstracts could be reviewed in the future. A total of 2043 matches were found and 1770 remained after excluding those with previous DWI convictions. Driver records were reviewed in 2010 and 2012, providing between 18 and 20 years of follow-up. Results : During the follow-up period, 16.5% of individuals were arrested for an impaired driving offense. Multivariate analysis suggested that recidivism was a function of several problems, including: alcohol problem severity, aggression, negative affect, drug problem severity, criminal history, and childhood delinquency. Conclusion : Impaired driving programs should assess for childhood delinquency, aggressive tendencies, and negative affect as these constructs, along with substance use, are evident among impaired drivers who recidivate. Interventions addressing aggression and negative affect may ultimately prove useful in reducing recidivism.